Diagnostic Tools in Allergic Rhinitis - Testera-Montes, Almudena; Jurado, Raquel; Salas, Maria; Eguiluz-Gracia, Ibon; Mayorga, Cristobalina (Frontiers in Allergy, 2021)
Allergic mechanisms account for most cases of chronic rhinitis. This condition is associated with significant impairment of quality of life and high indirect costs. The identification of the allergic triggers of rhinitis has been historically based on the performance of atopy test (skin prick test (SPT) and serum allergen-specific (s)IgE). Nevertheless, these tests only denote sensitization, and atopy and allergy represent two different phenomena. It is now clear that allergic phenotypes of rhinitis can exist in both atopic (allergic rhinitis, AR) and non-atopic (local allergic rhinitis, LAR) individuals. Moreover, both allergic phenotypes can coexist in the same rhinitis patient (dual allergic rhinitis, DAR). Therefore, a diagnostic approach merely based on atopy tests is associated with a significant rate of misdiagnosis. The confirmation of the allergic etiology of rhinitis requires the performance of in vivo test like the nasal allergen challenge (NAC). NAC is mandatory for the diagnosis of LAR and DAR, and helps decide the best management approach in difficult cases of AR. Nevertheless, NAC is a laborious technique requiring human and technical resources. The basophil activation test (BAT) is a patient-friendly technique that has shown promising results for LAR and DAR diagnosis. In this review, the diagnostic usefulness for chronic rhinitis of SPT, NAC, olfactory tests, serum sIgE, BAT and the quantification of inflammatory mediators in nasal samples will be discussed. The accurate performance of an etiologic diagnosis of rhinitis patients will favor the prescription of specific therapies with disease-modifying potential like allergen immunotherapy.